Allocation of allowable pollution load by using the bankruptcy solution rules - Ali Ahani (IWA Publishing, 2021)
Bankruptcy solution methods are widely used and efficient methods for conflict resolution which attract considerable attention in the area of solving conflicts related to water resources. However, most of the related studies have focused on the use of bankruptcy solution methods in solving quantitative water resources conflicts. In this study, four bankruptcy solution rules including proportional (PRO), constrained equal awards (CEA), constrained equal losses (CEL), and Talmud (TAL) rules were used to develop four models to allocate the allowable pollution loads to pollution sources. One of the novel aspects of the current study is to consider the amount of each flow discharge in addition to the pollution concentration of each pollution source. Evaluation of performances of the selected bankruptcy solution rules in a reach of Karun River in Iran showed that the CEA-based model can be considered as the most desirable option for small pollution sources whereas the CEL-based model seems to be the most appropriate option for large pollution sources. The models based on PRO and TAL rules provide results between those of CEA and CEL rules which can be considered as more probable options to reach agreement on between small and large pollution sources.